Bibliometric Analysis on Sustainability Accounting and Integrated Reporting Challenges - Judijanto, Loso; Haryanti, Titik; Kurniawan, Setia Budi (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of the academic literature on sustainability accounting and integrated reporting, aiming to uncover key themes, influential contributors, and emerging trends within the field. Drawing data from the Scopus database and visualizing relationships using VOSviewer, the analysis covers publications from 2013 to 2023. Results indicate that core concepts such as integrated reporting, sustainability reporting, and sustainable development serve as central pillars of scholarly discourse, interconnected with themes like ESG, accountability, and climate change. The research highlights a temporal evolution from environmental concerns toward governance-oriented frameworks and reveals that most contributions originate from Western institutions, particularly the United Kingdom and Italy. Despite a maturing body of literature, the study identifies underexplored areas, including biodiversity reporting, digital innovations, and practitioner-level implementation challenges. These findings offer valuable insights for scholars, practitioners, and policymakers seeking to advance the quality, comparability, and impact of sustainability disclosures in alignment with global sustainability goals.